2015
DOI: 10.1371/journal.pone.0143387
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Detoxification Supergene Families in the Mosquito Anopheles sinensis

Abstract: Anopheles sinensis is an important malaria vector in China and other Southeast Asian countries, and the emergence of insecticide resistance in this mosquito poses a serious threat to the efficacy of malaria control programs. The recently published An. sinensis genome and transcriptome provide an opportunity to understand the molecular mechanisms of insecticide resistance. Analysis of the An. sinensis genome revealed 174 detoxification genes, including 93 cytochrome P450s (P450s), 31 glutathione-S-transferases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 92 publications
0
30
0
Order By: Relevance
“…Previous studies have shown that GSH S‐transferase, carboxylesterases and peroxidases were involved in the resistance to DDT and malathion, [ 38,40 ] while GSH S‐transferases and cytochromes were associated with resistance to DDT, permethrin, deltamethrin, λ ‐cyhalothrin, and malathion. [ 41,42,43 ] Thioredoxin peroxidase was associated with resistance to deltamethrin [ 44 ] and acetyl‐CoA acyltransferase, enoyl‐CoA isomerase, and glutathione S‐transferase with resistance to organophosphate. [ 39 ] GSH S‐transferase and cytochromes were the most impacted by insecticide pressures in both climate regions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that GSH S‐transferase, carboxylesterases and peroxidases were involved in the resistance to DDT and malathion, [ 38,40 ] while GSH S‐transferases and cytochromes were associated with resistance to DDT, permethrin, deltamethrin, λ ‐cyhalothrin, and malathion. [ 41,42,43 ] Thioredoxin peroxidase was associated with resistance to deltamethrin [ 44 ] and acetyl‐CoA acyltransferase, enoyl‐CoA isomerase, and glutathione S‐transferase with resistance to organophosphate. [ 39 ] GSH S‐transferase and cytochromes were the most impacted by insecticide pressures in both climate regions.…”
Section: Discussionmentioning
confidence: 99%
“…We used available An. sinensis transcriptome data (BioProject Accession: PRJNA293400; http://www.ncbi.nlm.nih.gov/Traces/wgs/?val=GDKS01) from Zhou et al . to identify insecticide resistance‐associated CPs.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We used available An. sinensis transcriptome data (BioProject Accession: PRJNA293400; http://www.ncbi.nlm.nih.gov/Traces/ wgs/?val=GDKS01) from Zhou et al 33 to identify insecticide resistance-associated CPs. This approach generated transcriptome data from a deltamethrin-susceptible strain (DS strain) and a deltamethrin-resistant strain (DR strain).…”
Section: Transcriptomic Analysis Of Potential Resistance-associated Cpsmentioning
confidence: 99%
“…Although CYP4 and CYP9 families have been earlier reported to display insecticide detoxification activities, the CYP6 family has been implicated in insecticide resistance more often than any other CYP family to date [19]. It is found exclusively in insects and is the most extensively studied P450 group in insects [20].…”
Section: The Cyp6 Familymentioning
confidence: 99%